Multileveled Central Trust Management Approach using Fog Computing - Ayesha Irshad; Syed Zohaib Hassan; Ayesha Aslam; Kalsoom Ayaz; Jamaluddin Mir; Muhammad Awais Bawazir (Journal of Management Practices, Humanities and Social Sciences, 2021)
In the IoT environment, one of the biggest issues is the devices' anonymity and mobility, i.e., continuously joining and leaving networks. This research aims to explore certain strategies that will enable users to overcome these issues. Fog computing is reclined of central cloud services on multiple points near edge devices. Fog computing creates a decentralized computing architecture that acts as an intermediary between the cloud and the devices producing the data. This decentralized approach enables the users to locate resources in such locations that are closer to the devices. Cloud services are more effective when they are provided with low latency, storage issues are reduced, bandwidth is saved, and QoS is enhanced. Distributed fog nodes can cope with the mobility of edge nodes. Although both edge and fog computing can bring computing processes to such locations where data is created by eliminating the need for central storage, this approach gives rise to unprecedented issues that do not exist in centralized architecture like cloud computing. Anonymity can be addressed by identifying vulnerable devices and evaluating their trust level. This research work proposes a trust management scheme to develop a reliable IoT infrastructure in terms of trust. In the proposed model, trust is evaluated and managed on multiple levels to at the tain quality of services and give customers the confidence to share their confidential data online. This goal will help the users connect to the internet without losing control of their data integrity and confidentiality